PREFERENSI MASYARAKAT DALAM PEMANFAATAN BUS TRANS SARBAGITA SEBAGAI MODA ANGKUTAN UMUM DI KAWASAN SARBAGITA - Ida Ayu Gede Krisna Jayanthy; Ida Bagus Made Parsa (Pranatacara Bhumandala: Jurnal Riset Planologi, 2021)
Trans Sarbagita is a road-based mass public transportation system on a fixed and regular route network in the Sarbagita area. This study aims to determine the characteristics of the Trans Sarbagita bus mode in passenger service and the factors that influence people's preferences in using the Trans Sarbagita bus as a mode of public transportation in the Sarbagita area. Data collection was carried out through interviews and distributing questionnaires. This type of research uses a quantitative approach. The number of samples used was 65 respondents using the accidental sampling method. Data analysis techniques used factor analysis. The result of this research is that trans sarbagita is a public transport/bus rapid transit (BRT) that serves passengers according to the minimum service standard which was initiated to reduce the level of traffic congestion in the Sarbagita area. The percentage that affects people's preferences in using the Trans Sarbagita bus as a mode of public transportation in the Sarbagita area is 94.570% which can be explained by these four factors. Each factor is named as follows: factor 1 is called proximity bus stop factor to public facilities, factor 2 is called security, factor 3 is called a tariff, factor 4 is called operational schedule.